Liability for Criminal Acts of Promoting Online Gambling Through Electronic Media - Zaini, Zulfi Diane; Hasan, Okta Jaya (Postgraduate Program in Law, Universitas Pattimura, 2026)
Introduction: The development of information technology and social media has had a significant impact on the pattern of public interaction, including the emergence of the crime of promoting online gambling through electronic media. This phenomenon poses serious challenges for criminal law enforcement in Indonesia, especially in determining the criminal responsibility of perpetrators.Purposes of the Research: This study aims to analyze the factors that cause the occurrence of criminal acts of online gambling promotion through electronic media and examine the form of criminal responsibility of perpetrators based on the Tanjungkarang District Court Decision Number 785/Pid.Sus/2024/PN TJK.Methods of the Research: The research methods used are normative juridical and empirical juridical juridical the normative juridical approach is carried out through the study of laws and regulations, legal doctrine, and court decisions, while the empirical juridical approach is carried out through interviews with authorized law enforcement officials.Results Main Findings of the Research: The findings of the study show that the factors causing the occurrence of online gambling promotion crimes include internal factors in the form of intentionality and low legal awareness of the perpetrators, external factors in the form of economic needs and ease of access to social media, as well as combined factors in the form of misuse of information technology advances. Furthermore, the form of criminal responsibility of the perpetrator is based on the fulfillment of the elements of criminal acts, mistakes, the ability to be responsible, and the absence of justifiable or forgiving reasons, as stipulated in the Electronic Information and Transaction Law and the Criminal Code. The judge's decision is considered to have reflected the application of the principle of criminal responsibility in a proportionate and fair manner.